2012
DOI: 10.1590/s1415-47572012005000021
|View full text |Cite
|
Sign up to set email alerts
|

Multi-target siRNA based on DNMT3A/B homologous conserved region influences cell cycle and apoptosis of human prostate cancer cell line TSU-PR1

Abstract: Abnormal genome hypermethylation participates in the tumorigenesis and development of prostate cancer. Prostate cancer cells highly express DNA methyltransferase 3 (DMNT3) family genes, essential for maintaining genome methylation. In the present study, multi-target siRNA, based on the homologous region of the DNMT3 family, was designed for the in vitro investigation of its effects on the proliferation, migration, and invasion of TSU-PR1 prostate cancer cells. The consequential cell-cycle derangement, through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…DNA methyltransferase dysregulation has frequently been reported in malignant tumors, including leukemia, prostate cancer, and gastric cancer . We observed that treatment of SKOV3 and 3AO cells with 5‐Aza‐CdR resulted in increased miR‐145 levels, suggesting that miR‐145 expression in EOC cells might be regulated by DNA methylation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…DNA methyltransferase dysregulation has frequently been reported in malignant tumors, including leukemia, prostate cancer, and gastric cancer . We observed that treatment of SKOV3 and 3AO cells with 5‐Aza‐CdR resulted in increased miR‐145 levels, suggesting that miR‐145 expression in EOC cells might be regulated by DNA methylation.…”
Section: Discussionmentioning
confidence: 79%
“…DNA methyltransferase dysregulation has frequently been reported in malignant tumors, including leukemia, prostate cancer, and gastric cancer. [24][25][26] We observed that treatment of SKOV3 Increasing evidence has shown that these DNMT work together to maintain a normal methylation pattern, and deregulation of either one could promote malignancies. 27 More recently, DNMT3A has been reported to participate in epithelial-mesenchymal transition (EMT).…”
Section: Expression Of Hk2 and Dnmt3a In Ovarian Cancer Tissue Subcmentioning
confidence: 90%
“…Among the three DNMTs, DNMT3B has been consistently shown to increase its levels in transformed vs. normal prostate tissue, both in patient tumors and in cell lines [ 34 37 ] and its expression increase along with adverse clinical parameters [ 36 , 37 ]. Functional studies in siRNA cell lines, cadmium-transformed prostate epithelial cells and TRAMP mouse models [ 35 , 38 , 39 ], together with the association between PrCa risk and a polymorphism in DNMT3B leading to increased enzyme expression [ 40 ], have provided further support to this hypothesis. Thus, DNMT3B seems to be the most important DNMT driver in PrCa.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike DNMT1, which preferentially maintains established DNA methylation patterns after replication, DNMT3A and DNMT3B play a critical role in the de novo DNA methylation process [38]. DNMT dysregulation has been frequently reported in malignant tumors, including leukemia, prostate cancer, and gastric cancer [39][40][41]. However, elucidation of the role of dysregulated DNMTs in ovarian carcinogenesis is in its infancy.…”
Section: Discussionmentioning
confidence: 99%